PERHITUNGAN TAMPANG LINTANG DIFERENSIAL HAMBURAN ELASTIK ELEKTRON-ARGON PADA 10,4 EV DENGAN ANALISIS GELOMBANG PARSIAL - Settings Paken Pandiangan; Suhartono (Jurnal Matematika Sains dan Teknologi, 2004)
It has been calculated theoretically using the partial wave methods for the elastic scattering differential cross-section of electron-argon at 10.4 eV. The wave function from Schrodinger equation was computed by the Numerov integration methods. For simplicity of scattering system , the Gaussian potential form has been employed. For comparison between theoretical and experimental approach then we used the test. The for this research is 2.386 that shows this calculation is good.